Altruism predicts mating success in humans. (18th July 2016) - Arnocky, Steven; Piché, Tina; Albert, Graham; Ouellette, Danielle; Barclay, Pat
Abstract : In order for non‐kin altruism to evolve, altruists must receive fitness benefits for their actions that outweigh the costs. Several researchers have suggested that altruism is a costly signal of desirable qualities, such that it could have evolved by sexual selection. In two studies, we show that altruism is broadly linked with mating success. In Study 1, participants who scored higher on a self‐report altruism measure reported they were more desirable to the opposite sex, as well as reported having more sex partners, more casual sex partners, and having sex more often within relationships. Sex moderated some of these relationships, such that altruism mattered more for men's number of lifetime and casual sex partners. In Study 2, participants who were willing to donate potential monetary winnings (in a modified dictator dilemma) reported having more lifetime sex partners, more casual sex partners, and more sex partners over the past year. Men who were willing to donate also reported having more lifetime dating partners. Furthermore, these patterns persisted, even when controlling for narcissism, Big Five personality traits, and socially desirable responding. These results suggest that altruists have higher mating success than non‐altruists and support the hypothesis that altruism is a sexually selected costly signal of difficult‐to‐observe qualities.